A Systematic Review of Participatory Approaches in Flood Risk Management: Methods and Applications - Gita Rama Mahardhika; Adjie Pamungkas (Jurnal Penataan Ruang, 2024)
Flood risk management (FRM) increasingly integrates participatory approaches to enhance resilience and effectiveness by engaging local communities and stakeholders. This systematic review synthesizes findings from 22 peer-reviewed articles published between 2015 and 2024, highlighting the tools, stakeholders, levels of participation, outcomes, and challenges associated with participatory FRM. The review identifies key engagement tools such as participatory mapping, community workshops, and digital platforms, noting their varied effectiveness in different contexts. Stakeholder involvement spans residents, government agencies, and NGOs, with diverse contributions enhancing the contextual relevance and acceptance of FRM strategies. Levels of participation range from consultative to collaborative and fully empowering, with higher engagement linked to more resilient and adaptive outcomes, albeit requiring more resources and time. Outcomes demonstrate that participatory approaches improve community preparedness, enhance flood management plans, and integrate local knowledge effectively. However, challenges persist, including resource constraints, stakeholder conflicts, and communication barriers, necessitating adaptive management and innovative engagement strategies. The findings underscore the need for policymakers and practitioners to prioritize participatory methods to develop inclusive and robust FRM frameworks. Future research should focus on scalable participatory models, the integration of advanced technologies, and the evaluation of long-term impacts on community resilience, providing a roadmap for the enhanced application of participatory approaches in diverse contexts.